Efflux Pump Activity and Mutations Driving Multidrug Resistance in Acinetobacter baumannii at a Tertiary Hospital in Pretoria, South Africa - Noel-David Nogbou; Granny M. Nkawane; Khanyisa Ntshane; Charles K. Wairuri; Dikwata T. Phofa; Kagiso K. Mokgokong; Mbudzeni Ramashia; Maphoshane Nchabeleng; Lawrence C. Obi; Andrew M. Musyoki (International Journal of Microbiology)
Acinetobacter baumannii (A. baumannii) has developed several resistance mechanisms. The bacteria have been reported as origin of multiple outbreaks. This study aims to investigate the use of efflux pumps and quinolone resistance-associated genotypic mutations as mechanisms of resistance in A. baumannii isolates at a tertiary hospital. A total number of 103 A. baumannii isolates were investigated after identification and antimicrobial susceptibility testing by VITEK2 followed by PCR amplification of blaOXA-51. Conventional PCR amplification of the AdeABC efflux pump (adeB, adeS, and adeR) and quinolone (parC and gyrA) resistance genes were performed, followed by quantitative real-time PCR of AdeABC efflux pump genes. Phenotypic evaluation of efflux pump expression was performed by determining the difference between the MIC of tigecycline before and after exposure to an efflux pump inhibitor. The Sanger sequencing method was used to sequence the parC and gyrA amplicons. A phylogenetic tree was drawn using MEGA 4.0 to evaluate evolutionary relatedness of the strains. All the collected isolates were blaOXA-51-positive. High resistance to almost all the tested antibiotics was observed. Efflux pump was found in 75% of isolates as a mechanism of resistance. The study detected parC gene mutation in 60% and gyrA gene mutation in 85%, while 37% of isolates had mutations on both genes. A minimal evolutionary distance between the isolates was reported. The use of the AdeABC efflux pump system as an active mechanism of resistance combined with point mutation mainly in gyrA was shown to contribute to broaden the resistance spectrum of A. baumannii isolates.